Field survey on the conformity of equipment and environment for audiometric test in South Korean hospital - Wan-Ho Cho; Jihyun Lee; Chanbeom Kwak; Sunghwa You; Junghee Sagong; Do-Yun Kim; Young Joon Seo (Critical Public Health)
Although requirements and the detailed calibration process for the pure tone audiometers and associated transducers are specified in international documentary standards, traceable calibration, and uncertainty evaluation processes based on the international metrology system are still not widely employed in the conformity assessment for audiometric devices. In this study, the survey based on the actual measurements and investigation on the current status of the deviation distribution of output response level of audiometer through supra-aural headphone and background noise level of test environment is conducted in actually operating test facilities in Korean hospitals. The observation was conducted for 17 devices in 7 hospitals. A field survey was conducted to evaluate audiometric equipment and environments in South Korean hospitals. The survey involved the assessment of 17 devices across 7 hospitals. In the case of air-conduction, one or more frequencies exceeding the allowable range by more than the measurement uncertainty were observed in 13 devices, and there were 3 cases in which 3 or more frequencies were out of range. There were 11 cases where the difference exceeded the uncertainty range at one or more frequencies, and there were also 3 cases where the difference exceeded the uncertainty range at 3 or more frequencies. While ambient noise conditions were found to be generally compliant, however there were several cases having significant problem in self-generated noise induced by condition of electricity. Through this investigation, the issues and current status resulting from discrepancies between the measurement standard system and current conformity assessments was examined. Moreover, the urgency of integrating with the international measurement standard system in the field of audiology is investigated.